The Combination of Ethanol Extracts of Phyllanthus niruri Linn, Typhonium flagelliforme and Piper crocatum increase the Macrophage Phagocytosis In Vitro - Reynelda Juliani Sagala; Retno Murwanti (Majalah Obat Tradisional, 2020)
Research on the activity of Phyllanthus niruri Linn, Typhonium flagelliforme (Lodd.) Blume and Piper crocatum have been conducted and showed various immunomodulatory activity. This study aims to investigate the immunomodulatory activity of the combination of the ethanolic extracts of Phyllanthus niruri Linn, Typhonium flagelliforme (Lodd.) Blume, and Piper crocatum by determining its macrophages phagocytic index and macrophages phagocytic capacity. Therefore, such a combination could be an alternative drug to increase immune response. In this study, the extraction procedure was carried out through maceration by using an ethanolic solvent. Combinations of herbs ethanol extract were varied in four groups of combination, at three different concentrations of 1 μg/ml, 10 μg/ml, and 100 μg/ml for each group. Macrophages were isolated from the peritoneum cavity of male mice (Mus musculus), and its phagocytic activity was quantified through the Leijh method (1986). The phagocytic index and phagocytic capacity of macrophages were determined by using latex beads as a trigger of phagocytosis and compared with negative controls of media, DMSO, and four groups of ethanolic extract combinations in different concentrations. The results indicate that all of combination group ethanol extract with a concentration of 10 μg/ml was significantly (p<0.05) optimum activated phagocytic index. Therefore the combination of Phyllanthus niruri Linn, Piper crocatum, and Thyphonium flagelliforme (Lodd.) Blume ethanolic extract might be prospective to increase nonspecific immune response.